Pro brace x a study on an athletic shoe design that can be implemented on basketball, volleyball and football shoes, with an incorporated ankle bracing system, for active people who experience chronic ankle injuries - Oxales, Carlos Gabriel C.
Ankle sprains are the most common sports related injury. There are several cases occurring every day and they can happen to anybody. One way to prevent ankle sprains is by wearing an ankle brace. While wearing an ankle brace provides a quick fix to ankle sprains, they do not come without some issues. A lot of ankle braces are a hassle to wear and are bulky therefore changing the fit of one's shoes. They can also cause discomfort and pain from the different components of the brace. Ankle braces can also be very expensive; buying a pair can cost as much as buying a new pair of shoes. With these issues taken into account, this thesis aims to pinpoint the specific problems users have with ankle braces, identify effective ways of supporting the ankle and to develop a design that addresses these problems. ProBraceX was developed to provide a convenient, comfortable and secure experience for the user by creating an athletic shoe design with an incorporated ankle bracing, system, removing the need to use a separate apparatus but still providing ample support to the ankle as well as the performance features needed in physical activity, specifically in basketball, volleyball and football, the three most popular sports in the Philippines.